Students’ Perceptions during Integration of Computer Games in Primary Education: QoE Analysis - Toni Malinovski; Marina Vasileva; Vladimir Trajkovik (International Journal of Informatics and Communication Technology (IJ-ICT), 2014)
The integration of computer games in the primary school program is a challenging task which requires changes in the pedagogical approach and teaching practices. Since it is important to understand students, this study follows student-centered approach while evaluating different variables in computer game enhanced classes, which impact the overall students’ Quality of Experience (QoE). We involved a total of 114 students in several primary schools in Macedonia which participated in traditional and game-based learning environment. Students’ feedback was collected through surveys and the data set was analyzed with a path analysis model that illustrates relationships between relevant variables which influence students’ QoE in classes enhanced with computer games. We found that students’ motivation mostly influenced students’ QoE, which was also determined by the increased effectiveness and simplified way of learning. The research results correlated students’ QoE and learning outcomes during integration of computer games in primary schools, which were altogether increased against the traditional environment.